Hubungan Ekonomi Keluarga dengan Tingkat Pendidikan Anak di Desa Sibio-Bio Kecamatan Sibabangun - Samakmur, Samakmur; Rambey, Mara Judan; Vebrina, Dinda (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to determine the influence of family economics on children's education levels in Sibio-bio Village, Sibabangun District. The type of research used is descriptive research. The population in this study was 284 heads of families. The sampling technique uses simple random sampling. The data collection technique in this research uses questionnaires and documentation. Data analysis uses descriptive analysis and inferential statistical analysis. Then the data obtained in this research will be analyzed using Product Moment Correlation Test analysis, coefficient of determination, and t test. Based on calculations from the results of data analysis obtained using SPSS Software version 22, the value of t = 5.319, while the t table = 1.687, can be seen if the t count is greater than the t table (5.319> 1.687), with a significant value = 0.00 at the 95% confidence level. or 5% confidence level =0.05. In this way, it can be seen that the significant value is smaller than α = 0.05 (0.00 <0.05). From these results it is known that Ha is accepted and H0 is rejected. Thus, it is concluded that there is a significant influence between the family economy and the level of children's education in Sibio-bio Village, Sibabangun District.